If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 76 + -2x = 90 + -3x Solving 76 + -2x = 90 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 76 + -2x + 3x = 90 + -3x + 3x Combine like terms: -2x + 3x = 1x 76 + 1x = 90 + -3x + 3x Combine like terms: -3x + 3x = 0 76 + 1x = 90 + 0 76 + 1x = 90 Add '-76' to each side of the equation. 76 + -76 + 1x = 90 + -76 Combine like terms: 76 + -76 = 0 0 + 1x = 90 + -76 1x = 90 + -76 Combine like terms: 90 + -76 = 14 1x = 14 Divide each side by '1'. x = 14 Simplifying x = 14
| -5.3(4p+6)-2.9(2p-5)= | | Uw+un=xforu | | -40=7(1-x)+4(3x-3) | | 2(k-3)= | | 2x+3-4x+6=3 | | -6=2x+b | | 1/4a=1/3 | | 3x+8x-2x=18 | | 4(2x+1)=5x+3x+3 | | V=(3.14*r)h | | 105=7(7-r) | | 4(12b-6)+10b=-2(8b+12)+9b | | 5+3x=-4x-16 | | 15f=193.75 | | 8=40(5) | | 2x+40+5x=360 | | 4(2-t)=t-2 | | 4x-17=(3x+11) | | 3+4x=-3x+6 | | -4-X+1-(4-1)=-2-X(4) | | 9=-2+y | | (6p+5)=18+15 | | 4(m-5)=2(m+3)+4 | | 3n+5-2n=-2 | | -8n=-40 | | 3t^2-16t+26=0 | | 6/5(5k+2)=-36 | | 2x+40(5x)=360 | | 2(x+8)=14x | | -6(1+4n)=-6n+6(n-9) | | h(-4)=7-2(-4) | | 4x+17=180 |